Cell Migration Research Based on Organ-on-Chip-Related Approaches - Xiaoou Ren; David Levin; Francis Lin (Micromachines, 2017)
Microfluidic devices have been widely used for cell migration research over the last two decades, owing to their attractive features in cellular microenvironment control and quantitative single-cell migration analysis. However, the majority of the microfluidic cell migration studies have focused on single cell types and have configured microenvironments that are greatly simplified compared with the in-vivo conditions they aspire to model. In addition, although cell migration is considered an important target for disease diagnosis and therapeutics, very few microfluidic cell migration studies involved clinical samples from patients. Therefore, more sophisticated microfluidic systems are required to model the complex in-vivo microenvironment at the tissue or organ level for cell migration studies and to explore cell migration-related clinical applications. Research in this direction that employs organ-on-chip-related approaches for cell migration analysis has been increasingly reported in recent years. In this paper, we briefly introduce the general background of cell migration and organ-on-chip research, followed by a detailed review of specific cell migration studies using organ-on-chip-related approaches, and conclude by discussing our perspectives of the challenges, opportunities and future directions.